Post-stroke Rehabilitation Training with a Motor-Imagery-Based Brain-Computer Interface (BCI)-Controlled Hand Exoskeleton: A Randomized Controlled Multicenter Trial - Frolov, Alexander A.; Mokienko, Olesya; Lyukmanov, Roman; Biryukova, Elena; Kotov, Sergey; Turbina, Lydia; Nadareyshvily, Georgy; Bushkova, Yulia (Frontiers in Neuroscience, 2017)
Repeated use of brain-computer interfaces (BCIs) providing contingent sensory feedback of brain activity were recently proposed as a rehabilitation approach to restore motor function after stroke or spinal cord lesions. However, there are only a few clinical studies that investigate feasibility and effectiveness of such an approach. Here we report on a placebo-controlled, multicenter clinical trial that investigated whether stroke survivors with severe upper limb (UL) paralysis benefit from 10 BCI training sessions each lasting up to 40 minutes. A total of 74 patients participated: median time since stroke is 8 months, 25% and 75% quartiles [3.0; 13.0]; median severity of UL paralysis is 4.5 points [0.0; 30.0] as measured by the Action Research Arm Test , ARAT, and 19.5 points [11.0; 40.0] as measured by the Fugl-Meyer Motor Assessment, FMMA. Patients in the BCI group (n=55) performed motor imagery of opening their affected hand. Motor imagery-related brain electric activity was translated into contingent hand exoskeleton-driven opening movements of the affected hand. In a control group (n=19), hand exoskeleton-driven opening movements of the affected hand were independent of brain electric activity. Evaluation of the UL clinical assessments indicated that both groups improved, but only the BCI group showed an improvement in the ARAT’s grasp score from 0 [0.0; 14.0] to 3.0 [0.0; 15.0] points (p<0.001) and pinch scores from 0.0 [0.0; 7.0] to 1.0 [0.0; 12.0] points (p<0.001). Upon training completion, 21.8% (36.4%) of the patients in the BCI group improved their ARAT (FMMA) scores. The corresponding numbers for the control group were 5.3% (ARAT) and 15.8% (FMMA). These results suggests that adding BCI control to exoskeleton-assisted physical therapy can improve post-stroke rehabilitation outcomes. Both maximum and mean values of the percentage of successfully decoded imagery-related EEG activity, were higher than chance level. A correlation between the classification accuracy and the improvement in the upper extremity function was found. An improvement of motor function was found for all patients independently of duration, severity and location of the stroke. Clinical trial registration number: NCT02325947.